2012
DOI: 10.1111/joor.12008
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal‐supporting ability of individual maxillary and mandibular teeth

Abstract: This study aimed to analyse occlusal force, area and pressure for individual maxillary and mandibular teeth by assessing their occlusal-supporting abilities. Ninety-nine subjects (49 men and 50 women; average age, 24·7 ± 3·4 years; range, 20-37 years) performed maximal voluntary clenching twice for 3 s in both the intercuspal position and the intercuspal position with sliding movement from edge-to-edge occlusion, with a pressure-sensitive sheet placed between the maxillary and mandibular dental arch. Occlusal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Wear tests were carried out over 1200 cycles with a constant load of 5 N. Although this force represents moderate contact forces between teeth [22,26], the corresponding maximum Hertzian contact pressure (assuming a Young's modulus of enamel of 50 GPa [31,32]) between the steel ball and tooth sample is about 430 MPa and 5-9 times higher than contact stresses measured during tooth clenching [33], thus reflecting a worst case simulation of tooth-tooth contact and attrition-induced wear. The chosen cycle number is equivalent to a total sliding distance of 2.4 m and reflects frequent tooth-tooth contacts in view of typical daily chewing rates [14,34,35].…”
Section: Wear and Friction Testsmentioning
confidence: 99%
“…Wear tests were carried out over 1200 cycles with a constant load of 5 N. Although this force represents moderate contact forces between teeth [22,26], the corresponding maximum Hertzian contact pressure (assuming a Young's modulus of enamel of 50 GPa [31,32]) between the steel ball and tooth sample is about 430 MPa and 5-9 times higher than contact stresses measured during tooth clenching [33], thus reflecting a worst case simulation of tooth-tooth contact and attrition-induced wear. The chosen cycle number is equivalent to a total sliding distance of 2.4 m and reflects frequent tooth-tooth contacts in view of typical daily chewing rates [14,34,35].…”
Section: Wear and Friction Testsmentioning
confidence: 99%
“…The mandibular first molar is the earliest permanent tooth appearing in the mouth and guides the development of the jaw . Analysis of its biomechanics provides understanding about tooth and periodontal functional patterns during chewing, and thus the evaluation of masticatory functions . To precisely define the stress/strain field of a molar during clenching, it is critical to build a model that incorporates the structure geometry, tissue properties and the acting forces on the mandibular system .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we analyzed the occlusal force, area, and pressure of individual maxillary and mandibular teeth and assessed their OSAs. We concluded that the occlusal pressure of individual teeth can be used as an indicator of OSA [6].…”
Section: Introductionmentioning
confidence: 89%